PENGARUH INFLASI, SUKU BUNGA DAN NILAI TUKAR RUPIAH (KURS) TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DI BURSA EFEK INDONESIA TAHUN 2013-2022 - Oktaviyani; Dewi Nari Ratih Permada (Journal of Research and Publication Innovation, 2025)
This study aims to determinate whether there is an inflation rate, interest rate and the Rupiah exchange rate on the Composite Stock Price Indeks on the Indonesia Stock Exchange in 2013-2022. This type of research uses quantitative research. The data used is secondary data with a time series type for the period 2013-2022 from the website www.idx.co.id and www.bi.co.id. The analytical method used is multiple linear regression analysis, classical assumption test, f test (simultaneous), t test (partial), coefficient of determinanion (R2) via IBM SPSS statistics 26. The results of thie research show that partial Inflaion has a posiive and significant effect on the CSPI with a value of |Tcount │-2.655│ > Ttable 1.980| with a significance of 0,0009 < 0,05, While Interest Rates have a negative and insignificant effect on the CSPI with value |Tcount │-1.505│ < Ttable 1.980| with a significance of 0,135 > 0,05, while the Rupiah Exchange Rate has a positive and significan effect on the CSPI with value |Tcount 4.224 > Ttable 1.980|with a significant of 0,001 < 0,05. Simultaneously Inflation, Interest Rate and the Rupiah Exchange Rate have a significant effect on the CSPI with value |Fcount 21.311 > Ftable 2.684| with a significance of 0,001 < 0,05. The coefficient of determination influence from this research in 0.342 or 34,2%, which means that the dependent variable is influenced by the independent variable, while the rest is influenced by other variables not explained in this research.